Smilax glabra Roxb. flavonoids protect against pathological cardiac hypertrophy by inhibiting the Raf/MEK/ERK pathway: In vivo and in vitro studies. (28th June 2022) - Fu, Danting; Zhou, Jiangfeng; Xu, Shanchun; Tu, Jue; Cai, Yueqin; Liu, Jingyan; Cai, Zhaowei; Wang, Dejun
Abstract: Ethnopharmacological relevance: Smilax glabra Roxb., the dry rhizome of Sarsaparilla, which is also known as Tu fuling (TFL) in China, is a well-known traditional CHINESE medicine that is widely used for detoxication, relieving dampness and as a diuretic. We have previously shown that the extracted TFL flavonoids (designated TFLF) possess anti-cardiac hypertrophy effects in vitro . However, the anti-cardiac hypertrophy effects of TFLF in vivo and the underlying mechanisms remain to be elucidated. Aim of the study: To reveal the underlying therapeutic mechanism of TFLF on cardiac hypertrophy by using transverse aortic constriction (TAC) model and cellular assays in vitro . Material & methods: Cardiac hypertrophy was replicated by TAC surgery in rats or by isoprenaline treatment of rat H9C2 myocardial cells in vitro . Cardiac structure and function were evaluated by echocardiographic and hemodynamic examinations in vivo and histological analysis of tissues ex vivo . Biochemical kits and quantitative PCR were used to analyze markers of cardiac hypertrophy. Expression and phosphorylation of key proteins in the Raf/MEK/ERK pathway were quantified by Western blotting. We further confirmed our findings in H9C2 rat cardiomyocytes treated with isoprenaline and the ERK inhibitor in vitro . Results: TFLF attenuated cardiac hypertrophy and fibrosis and improved cardiac dysfunction in TAC rats. TFLF treatment induced a strong reduction in serum NT-proBNP levels. Cardiac hypertrophy marker gene ( ANP, BNP and β-MHC ) expression and the phosphorylation levels of c-Raf and ERK1/2 were decreased by TFLF treatment. TFLF also protected H9C2 cells from isoprenaline-induced hypertrophy in vitro via a similar molecular mechanism as that observed in the rat heart. Moreover, pretreatment with TRLF and the ERK inhibitor further inhibited the mRNA overexpression of hypertrophic genes in vitro . Conclusions: TFLFs may protect against pathological cardiac hypertrophy via negative regulation of the Raf/MEK/ERK pathway. Thus, TFLFs are implicated as a potential pharmacological agent for treating cardiac hypertrophy in clinical practice. Graphical abstract: Image 1